EFEKTIFITAS TEPUNG IKAN LOKAL DALAM PENYUSUNAN RANSUM PAKAN IKAN NILA Oreochromis niloticus - Bagus Dwi Hari Setyono; Andre Rachmat Scabra; Muhammad Marzuki; Sudirman Sudirman (Jurnal Perikanan Unram, 2020)
In the aquaculture industry, feed plays a vital role because more than 50% of the production cost is for feed procurement costs. The feed used must not only contain good nutritional content, but also be economically affordable. The better the quality of the feed, accompanied by the cheaper the feed, the success of fish production activities can be guaranteed. The purpose of this study was to increase the use of local fish meal as a substitute for commercial fish meal in tilapia feed formulations. This study used a completely randomized design (CRD) model consisting of four treatments and three replications. The treatment applied was feeding the fish with artificial feed made from a combination of local fish meal with commercial fish meal at different doses. The treatments in this study werea (commercial fish meal 30% + local fish meal 0%), B (commercial fish meal 20% + local fish meal 10%), C (commercial fish meal 10% + local fish meal 20%), and D (commercial fish meal 0% + local fish meal 30%). The results of the analysis of variance (ANOVA) test showed that the treatment had no significant effect on the value of survival rate (SR), but had a significant effect on the value of Specific Growth Rate (SGR), Feed Conversion Ration (FCR) and blood glucose levels (GD). The SR values of treatment A, B, C, and D were 96.7%, 96.7%, 96.7%, and 100%, respectively. The SGR values of treatment A, B, C, and D were 0.15% / day, 0.24% / day, 0.29% / day, 0.35% / day, respectively. The FCR values of treatment A, B, C, and D were 10.25, 7.47, 5.00, and 4.16, respectively. The GD values of treatments A, B, C, and D were 217.67 mg / dL, 160.33 mg / dL, 155.00 mg / dL, and 132.67 mg / dL, respectively. The water quality during the research was still classified in the optimum range of tilapia rearing water quality, namely temperature 29.0?31.9 oC, pH 7.0?8.2, DO 4.3?5.9 mg / L, and ammonia 0.0011-0.0293 mg / L. The conclusion of this research activity is, the use of fish feed using the formulation of local fish meal as a raw material can be used as a substitute for commercial fish meal.